CEFTA-2006 towards creation of a regional economic area - Kikerkova, Irena; Toshevska trpchevska, Katerina; Makrevska disoska, Elena (“St. Kliment Ohridski” University –Bitola, 2018)
The functioning of CEFTA-2006 within the 10-year period of its creation pointed out the low capacity and unsatisfactory performance of the region in regard of trade liberalization. In July 2017 under the Berlin Process, member-states decided to enhance mutual cooperation by taking the free trade area to a higher level – regional economic area - which should provide full liberalization in trade in goods and services; free movement of capital and labor and digital integration. For this purpose an Agreement on Amendment of and Accession to the Central European Free Trade Agreement is issued in which a new Protocol 5 on trade in goods is integrated, while Protocol 6 on trade in services is also planned to be adopted and integrated.The paper is going to give a brief overview of the achieved trade integration within CEFTA-2006; observation on the obstacles for full trade liberalization and trade facilitation by detection of non-trade barriers; and analysis of Protocol 5 that concerns deeper trade liberalization, as well as trade facilitation. The paper is going to give a brief overview of the achieved trade integration within CEFTA-2006; observation on the obstacles for full trade liberalization and trade facilitation by detection of non-trade barriers; and analysis of Protocol 5 that concerns deeper trade liberalization, as well as trade facilitation.
Keywords: CEFTA-2006; regional economic area; non-trade barriers; trade facilitation; Protocol 5